The Effect Of Managerial Ownership And Institutional Ownership On Financial Performance of LQ 45 Companies Listed On The Indonesia Stock Exchange (IDX) - Jusman Kasih Abdi Lase; Rina Rina; Afrinanda Afrinanda (PT. Hafasy Dwi Nawasena, 2025)
The purpose of this study is to determine how managerial ownership and institutional ownership partially and simultaneously affect the financial performance of companies listed in the LQ 45 on the Indonesia Stock Exchange (IDX) in 2019-2023. The approach used in this study is an associative approach, and the analysis technique used is quantitative data. The population in this study is all companies listed in the LQ 45 on the Indonesia Stock Exchange (IDX) in 2019-2023. The method used in determining the sample is a purposive sampling method using certain criteria. With the purposive sampling method, the sample used is 10 companies out of 45 companies over the 5 years of the study, so the data used is 50 samples. From the results of this study, managerial ownership partially does not affect financial performance with the test results being the calculated t value (0.339) < t table (2.01174) and a significant value of 0.691> 0.05, while institutional ownership affects financial performance with the test results being the calculated t value (-2.793)> t table (2.01174) and a significant value of 0.008 <0.05. Simultaneously, managerial ownership and institutional ownership affect financial performance with the test results being the calculated f value (5.127)> f table (3.20) and a significant value of 0.010 <0.05.